SOME PATHOGENETIC ASPECTS OF HYPERTHROPHY AND INFLAMMATION OF PHARYNGEAL TONSILS IN CHILDREN - V. N. Zorina; I. I. Klimova; A. C. Vyshlova; R. M. Zorina; T. G. Riabicheva; N. A. Zorin (Медицинская иммунология, 2014)
We have measured total levels of alpha-2-macroglobulin (α2-MG), its immune complexes with IgG (α2-MG-IgG), along with IL-6, IL-8, IL-10, TNFα, lactoferrin (LF) and alpha-1-antitrypsin (AT) contents in blood sera of children with verified chronic adenoiditis (ChA), pharyngeal tonsil hypertrophy (PhTH), and in sera of healthy children. It was shown, that α2-MG, α2-MG-IgG, AT, IL-10 serum concentrations in ChA and PhTH were significantly increased in comparison with appropriate values in healthy children. Moreover, we have detected significant increase in LF, and slight decrease of IL-6 and IL-8 contents in sera of ChA patients. All general trends of detected changes were similar for both diseases, but some changes proved to be differently expressed. In ChA, however, we found higher levels of circulating α2-MG molecules in circulation, some deficiency in IL-6 and IL-8, and significant abundance of IL-10 and LF at the beginning of ChA, thus resulting into a chronic disorder. In PhTH patients, there was no such remarkable abundance of α2-MG and LF in circulation, and no deficiency in IL-6 and IL-8, but higher levels of damaged α2-MG molecules complexing with IgG, total α2-MG, AT and IL-10 excess may provoke distinct metabolic changes and compensatory proliferation of tissues in this disorder.